On multipliers of supplementary difference sets and D-optimal designs for n ≡ 2mod4 - Georgiou S.; Koukouvinos C. (Utilitas Mathematica, 1999)
We investigate multipliers of 2 - v; k1, k2; λ supplementary difference sets, where v = 2q2+2q+1, k1 = k2 = q2, λ = q(q - 1), for q = 2,4,5,6,7,8,9, and then we construct D-optimal designs of orders 26,82,122,170,226,290,362.